Perkembangan Masa Remaja - Tasya Alifia Izzani; Selva Octaria; Linda Linda (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research discusses the development of adolescence which is a transition phase from childhood to adulthood. This phase involves significant physical, cognitive, emotional, and social changes. Physical development is characterized by rapid body growth and sexual development. Meanwhile, cognitive development includes an increase in abstract thinking and problem solving abilities. Adolescent emotional development often includes emotional turmoil and a search for self-identity. On the social side, adolescents experience an increase in interactions with peers and exploration of romantic relationships. Internal and external factors such as family environment, peers, and social media also influence adolescent development. This study highlights the importance of a deep understanding of adolescence to support holistic adolescent growth and development.